Ubiquitin-related modifier SUMO1 and nucleocytoplasmic transport - Pichler, Andrea; Melchior, Frauke (Traffic, 2002)
Small ubiquitin related modifier SUMO-1 and its homologs can be conjugated to a large number of cellular proteins. This involves an enzymatic cascade that resembles ubiquitination, and the modification can be reverted by isopeptidases. SUMOylation does not lead to degradation but instead appears to regulate protein/protein interactions, intracellular localization and protects some modified targets from ubiquitin-dependent degradation. Data collected for more than 30 different target proteins point to two cellular processes, nucleocytoplasmic transport and intranuclear targeting, in which SUMO plays an active role. Here we will focus on links between SUMO and nuclear transport.
Gesehen am 17.08.2023